400 Poison prevention practices and medically attended poisoning in young children: multicentre case-control study. (1st September 2016) - Kendrick, Denise; Majsak-Newman, Gosia; Benford, Penny; Coupland, Carol; Timblin, Clare; Hayes, Mike; Goodenough, Trudy; Hawkins, Adrian; Reading, Richard
Abstract : Background: Childhood poisonings are common, placing a substantial burden on health services. Education and provision of cupboard/drawer locks improves poison prevention practices but it is unclear if this reduces poisoning risk. This study quantifies associations between poison prevention practices and medically attended poisonings in 0–4 year olds. Methods: Multicentre case-control study conducted at hospitals, minor injury units and family practices from four study centres in England between 2010 and 2013. Participants comprised 567 children presenting with unintentional poisoning occurring at home, and 2320 control participants matched on age, sex, date of event and study centre. Parents/caregivers provided data on safety practices, safety equipment use, home hazards and potential confounders, by means of self-completion questionnaires. Data were analysed using conditional logistic regression. Results: Compared with controls, parents of poisoned children were significantly more likely not to store medicines out of reach (adjusted odds ratio (AOR) 1.59; 95% CI: 1.21, 2.09; population attributable fraction (PAF) 15%), not to store medicines safely (locked or out of reach (AOR 1.83; 95% CI: 1.38, 2.42; PAF 16%) and not to have put all medicines (AOR 2.11; 95% CI: 1.54, 2.90; PAF 20%) or household products (AOR 1.79, 95% CI: 1.29, 2.48; PAF 11%) away immediately after use. Conclusions: Not storing medicines out of reach or locked away and not putting medicines and household products away immediately after use increased the odds of secondary care attended poisonings in 0–4 year olds. If associations are causal, implementing each of these poison prevention practices could prevent between 11% and 20% of poisonings.